Radiological Study Of Mineralization Of Third Molars For Estimation Of Age Using Demirjian Method (Journal of Forensic Medicine & Toxicology, 2026)
Accurate age estimation is necessary in forensic practice, particularly during late adolescence when legal distinctions between juvenile and adult status carry significant implications. Dental parameters are widely regarded as reliable indi cators of age, as tooth development is minimally affected by environmental and systemic factors. Among these, third molar mineralization remains especially valuable in individuals between 15 and 25 years of age due to its prolonged and variable developmental timeline. This radiological study was undertaken to evaluate the relationship between third molar mineralization stages and chronological age using Demirjian’s method, and to assess possible variations related to sex. The study included 200 indi viduals (100 males and 100 females) aged 15–25 years, all of whom were born and residing in Mumbai. Chronological age was confirmed using official birth records. Orthopantomograms were obtained for each subject, and all four third molars were assessed according to Demirjian’s eight-stage mineralization system. Statistical analysis was performed using SPSS software. Early mineralization stages (A–C) were not observed in the study population. No statistically significant differences were found between males and females or between the right and left sides in either jaw. Maxillary third molars showed marginally earlier mineralization compared to mandibular molars. A strong positive correlation was observed between mineralization stages and chronological age, allowing the derivation of regression equations for age estimation. Stage H was consistently associated with attainment of adulthood. The study supports the relevance of Demirjian’s method for age estimation in late adolescence and early adulthood, where reliable documentary evidence is unavailable.
Keywords: Age estimation; Third molar mineralization; Demirjian method; Orthopantomogram; Forensic odontology